“I’m told I’m famous on the internet”: Henri the Cat and the Critical Possibility of Anthropomorphism - Myers, Caitlin Rose (Humanimalia, 2015)
This paper examines the phenomenon of feline Youtube celebrity in the context of human/nonhuman animal interactions and the construction of the posthuman subject. I argue that “Henri,” or Henry, the Youtube star, presents the particularized difficulties of both human and nonhuman animals, including Derridean “nonpower,” manipulation through medium (virtual or otherwise), and the performativity of identity. While Derrida explicitly derides anthropomorphism as “a moralizing subjection, a domestication” in his The Animal That Therefore I Am,I will further argue for the critical possibilities of anthropomorphism using popular responses to the Henri videos alongside recent theoretical perspectives that argue for its necessity. This multimedia presentation aims to demonstrate that it is possible to draw the public fascination with feline celebrities into conversation with questions of what it means to be “human” or “animal,” as well as what it means to present oneself as “being” in a posthuman world.